Fibrodysplasia Ossificans Progressiva: A Case Report - Dionisio, Filipa (2024)
Fibrodysplasia ossificans progressiva (FOP) is a rare autosomal dominant disease, related to the ACVR1/ALK2 gene mutation that activates the aberrant formation of bone tissue. It is characterized by a gradual limitation of the range of joint movement due to the heterotopic osteogenesis in the connective tissue. As the disease progresses, difficulty in global mobility increases, restricting the expandability of the thoracic cavity, impacting lung and heart function. A young man, born in Guinea Bissau, evacuated to Portugal at the age of 2. He was observed in a medical appointment at Alcoitão Rehabilitation Medical Center at the age of 14. On objective examination, he presented great limitation of joint range of motion, performed autonomous walking with a flexed hip posture, little waist dissociation, forward center of gravity and increased risk of falling. Hospitalization was proposed to optimize his functionality. FOP is a challenge for Physical and Rehabilitation Medicine. Occupational therapy and hydrotherapy contribute to improving functionality, but the study and prescription of support products are essential to maximize patient autonomy.